2008
DOI: 10.1002/bmc.1108
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a sensitive LC‐MS/MS method with electrospray ionization for quantitation of pramipexole in human plasma: application to a clinical pharmacokinetic study

Abstract: A highly sensitive and specific LC-MS/MS method has been developed and validated for the estimation of pramipexole (PPX) with 500 microL human plasma using memantine as an internal standard (IS). The API-4000 was operated under multiple-reaction monitoring mode (MRM) using the electrospray ionization technique. Solid-phase extraction was used to extract PPX and IS from human plasma. The resolution of peaks was achieved with 0.01 m ammonium acetate buffer (pH 4.4):acetonitrile (30:70, v/v) on a Discovery CN col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 5 publications
3
9
0
1
Order By: Relevance
“…As expected, PPX and IS were well retained on the cyano column, while retention time was found to be inconsistent on Ultimate ® Hilic column due to its complicated separation mechanism such as partition between the mobile phase eluent and a water-enriched liquid layer on the hydrophilic stationary phase, hydrogen bonding, dipole-dipole and ion-exchange [23]. These findings were also consistent with previous reports in which either a Discovery CN column or a Zorbax SB-CN column was used for chromatographic separation of PPX [12,14]. However, the retention time, peak shape and MS response were also strongly influenced by the composition of the mobile phase when Ultimate ® XB-CN column was utilized for analysis.…”
Section: Optimization Of Chromatographic Conditionssupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, PPX and IS were well retained on the cyano column, while retention time was found to be inconsistent on Ultimate ® Hilic column due to its complicated separation mechanism such as partition between the mobile phase eluent and a water-enriched liquid layer on the hydrophilic stationary phase, hydrogen bonding, dipole-dipole and ion-exchange [23]. These findings were also consistent with previous reports in which either a Discovery CN column or a Zorbax SB-CN column was used for chromatographic separation of PPX [12,14]. However, the retention time, peak shape and MS response were also strongly influenced by the composition of the mobile phase when Ultimate ® XB-CN column was utilized for analysis.…”
Section: Optimization Of Chromatographic Conditionssupporting
confidence: 93%
“…Another method based on capillary electrophoresis with laser-induced fluorescence detection was developed for the concentration determination of PPX in human urine [11]. Due to the lack of sufficient assay selectivity and sensitivity, several LC-MS/MS methods were subsequently developed for the quantification of PPX in human plasma [12][13][14][15]. M. Yadav et al has summarized the advantages and shortcomings of these reported analytical assays for the quantitation of PPX in biomatrices [15].…”
Section: Introductionmentioning
confidence: 99%
“…For S ‐pramipexole, the pharmacokinetic studies revealed a maximum plasma concentration between 5.44 and 7.17 μg/L on healthy volunteers, who were treated with the highest therapeutic dose of 4.5 mg per day . Until now, several chromatographic or electrochemical methods devoted to analysis of S ‐pramipexole were proposed from complex biomatrices using HPLC–UV , liquid or ultra‐performance liquid chromatography coupled with tandem mass spectrometry , GC–MS , voltammetric detection of carbon nanotube electrode , CE . The main analytical problem in the detection of S ‐pramipexole is related to matrix effect of the sample which limited direct measurements by the analytical instruments.…”
Section: Introductionmentioning
confidence: 99%
“…The retention times of PPX and IS were 1.39 and 1.14 min, respectively, under gradient elution, see typical chromatograms of PPX and IS in BSupplemental Materials (Fig. 4).B ased on previous reports (22,23), a Waters Xevo TQ-S triple-quadrupole mass spectrometer (Waters Corporation, Milford, MA, USA) equipped with an electrospray ionization source was used in positive ion mode with selected reaction monitoring for the quantitative analysis of PPX. The spray voltage was set at 4.0 kV, and the capillary temperature was maintained at 320°C.…”
Section: Uplc-ms/ms Methodsmentioning
confidence: 99%